Quality of Chicken Sausage during Storage with Addition of Andaliman Fruit Powder - Julianti, Elisa; Lubis, Zulkifli; Hilman, Adrian (Jurnal Gizi dan Pangan, 2023)
The study aimed to evaluate the impact of Andaliman Fruit Powder (AFP) concentrations ranging from 0.5 to 1.5% on the quality of chicken sausages over a 4-week storage period. The result showed that a higher concentration of AFP had a significant (p<0.05) increase in total phenolics and total flavonoids, while the total microbes and free fatty acid content decreased. There were no significant differences (p>0.05) observed in the protein content, pH, texture, and panelists' acceptance of color, aroma, and taste in comparison with the control. The incorporation of 1.5% AFP can be applied to maintain the quality of chicken sausage during storage at 10°C.